Uji Ketahanan Tujuh Kultivar Jagung (Zea mays L.) Terhadap Penyakit Bulai (Peronosclerospora spp.) - Budi Setiadi Daryono; Anisa Parazulfa; Purnomo Purnomo (Biogenesis: Jurnal Ilmiah Biologi, 2018)
Maize (Zea mays L.) is one of important food in Indonesia. Java Downy Mildew is a plant disease caused by Peronosclerospora spp. This specific fungus attacks corn plants, especially the leaves. The purpose of this study was to examine maize cultivars resistance to Java Downy Mildew.  This research was conducted at the land owned by Agrotechnology Innovation Center (PIAT) UGM located in Kalitirto Village, Berbah Subdistrict, Sleman Regency, Special Region of Yogyakarta. The main ingredients used in this study included maize with 7 different cultivars: Gama GS, Gama SG, Bisi 816, Pioneer 21, Lagaligo, Talenta, and Pulut. This research was conducted using Randomized Block Design with 7 treatments and 2 replications. The results showed that Talenta, Lagaligo and Bisi-816 were resistant to downy mildew. Pioneer-21 quite resistant to downy mildew. Cultivars Gama GS, Gama SG and Pulut were not resistant to downy mildew. This study provides new information related to the infection of downy mildew especially in Yogyakarta.